2020
DOI: 10.3390/ph14010026
|View full text |Cite
|
Sign up to set email alerts
|

Central Serous Chorioretinopathy Classification

Abstract: Central serous chorioretinopathy is characterized by an idiopathic neurosensory detachment of the retina. This narrative review aims to discuss the classification system used for central serous chorioretinopathy. Based on our current knowledge, there is no universally adopted classification system. This is the result of the unknown aspects related to pathogenesis and clinical spectrum and evolution. The best option could be to aggregate multimodal pieces of information alongside temporal and phenotypic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(156 reference statements)
0
5
0
Order By: Relevance
“… 16 However, CSC was easy to transform into a chronic course or recurrent attack, which would cause the detachment of RPE in the macular region and eventually lead to the decline of visual function. A previous study had pointed out that about 12.8% of patients with chronic CSC would eventually suffer from permanent blindness in both eyes, 2 thus it is important to develop several prognostic factors. It was reported that psychological stress, type-A behavior pattern, steroid use, and pregnancy are reported diagnostic and prognostic factors of CSC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 However, CSC was easy to transform into a chronic course or recurrent attack, which would cause the detachment of RPE in the macular region and eventually lead to the decline of visual function. A previous study had pointed out that about 12.8% of patients with chronic CSC would eventually suffer from permanent blindness in both eyes, 2 thus it is important to develop several prognostic factors. It was reported that psychological stress, type-A behavior pattern, steroid use, and pregnancy are reported diagnostic and prognostic factors of CSC.…”
Section: Discussionmentioning
confidence: 99%
“…1 Most CSC cases remitted spontaneously within 3 months, but it's easy to relapse and cause visual impairment. 2 The classifications of CSC are based on duration of the disease as well as multimodal imaging-based examinations, 3 and both classification methods were helpful in advanced CSC management. The initial CSC classification is simply based on CSC duration and the CSC cases are divided into two forms, the acute and chronic ones, according to the duration of the SRF presentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C entral serous chorioretinopathy (CSC) is a chorioretinal disease characterized by limited serous detachment of the neurosensory retina at the posterior pole, often associated with varying degrees of low-grade focal leakage at the level of the altered retinal pigment epithelium (RPE) [1][2][3] . These histological, structural, and vascular abnormalities lead to clinical symptoms such as micropsia with a partial reduction in visual acuity and mild colour discrimination [4][5][6] . This condition is predominantly seen in middle-aged males [7] .…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by a spontaneous resolution in the majority of patients, but the severe visual loss has been reported in 5% of cases [4]. Acute CSC is traditionally managed by observation alone, but the use of recent advances in technology, including adaptive optics, multifocal electroretinography, and microperimetry, have revealed significant anatomic and functional loss, even in eyes with a single episode of spontaneously resolved CSC with good Visual Acuity (VA) [5][6][7][8][9]. Because most CSC patients are of working age, visual symptoms may considerably interfere with their daily activities.…”
Section: Introductionmentioning
confidence: 99%